Workplace bullying among nurses in the Jordanian private hospitals - Abuseif, Sami Farhan Ahmad (2016)
Workplace bullying is a wide spread phenomenon that constitutes negative impact to individuals and organizations. Prior studies have proven the negative implications of bullying behaviors in workplaces on the health of the victims and the performance of organizations. This study aims to examine the relationship between the perception of injustice, job insecurity, trait anger, and negative affectivity with workplace bullying among nurses in private hospitals in Jordan. The role of self-control as the moderating factor in this relationship is also examined. The study used a survey method and questionnaires were distributed to 500 nurses at five private hospitals in Amman, Jordan. The data then were analysed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) and it is found that there is a positive and significant relationship between the perception of distributive injustice, perception of interactional injustice, trait anger, negative affectivity and workplace bullying. On the contrary, it is discovered that there is no positive and significant relationship between perception of procedural injustice and workplace bullying; and perception of job insecurity and workplace bullying. However, it is discovered that self-control serves as moderator in the relationship between the perception of distributive injustice and workplace bullying; and between trait anger and workplace bullying. In general, these findings support the view that self-control can override predispositions of individuals to engage in workplace bullying. Theoretical and practical implications of this study are also discussed